Vermeer and His Milieu : A Web of Social History - Montias, John Michael, 1928-2005 (Book collections on Project MUSE., 1989)
This book is not only a fascinating biography of one of the greatest painters of the seventeenth century but also a social history of the colorful extended family to which he belonged and of the town life of the period. It explores a series of distinct worlds: Delft's Small-Cattle Market, where Vermeer's paternal family settled early in the century; the milieu of shady businessmen in Amsterdam that recruited Vermeer's grandfather to counterfeit coins; the artists, military contractors, and Protestant burghers who frequented the inn of Vermeer's father in Delft's Great Market Square; and the quiet, distinguished "Papists Corner" in which Vermeer, after marrying into a high-born Catholic family, retired to practice his art, while retaining ties with wealthy Protestant patrons. The relationship of Vermeer to his principal patron is one of many original discoveries in the book.